2000
DOI: 10.1002/(sici)1097-4628(20000531)76:9<1457::aid-app9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Copolymeric network crown ether resins with pendent functional group: Synthesis and adsorption for metal ions

Abstract: Three network crown ether resins with a high content of pendent functional groups were prepared and characterized by IR, elemental analysis, and thermal analysis. The slight variance of the thermal stability of the resins was related to the kind and content of the pendent functional group. The adsorption capacity of the resins for Mg(II), Cu(II), Co(II), Pb(II), and Hg(II) was determined. Toward Hg(II), the adsorption capacity of the resins was high and the adsorption process was easy and spontaneously perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, the stoichiometric coordination of metal ions is expected, since the adsorbents have a molecular nature. In contrast, previous studies on synthetic polymers [14][15][16][17][18][19][20] have revealed that the ratio of N(adsorbate ion)/N(ionic pendant function) is far from stoichiometric and the capacity is, in most cases, below 1 mmol g À1 . Amine pendants have been often studied for the adsorption of oxyanions such as arsenate and chromate.…”
Section: Hideaki Yoshitakementioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, the stoichiometric coordination of metal ions is expected, since the adsorbents have a molecular nature. In contrast, previous studies on synthetic polymers [14][15][16][17][18][19][20] have revealed that the ratio of N(adsorbate ion)/N(ionic pendant function) is far from stoichiometric and the capacity is, in most cases, below 1 mmol g À1 . Amine pendants have been often studied for the adsorption of oxyanions such as arsenate and chromate.…”
Section: Hideaki Yoshitakementioning
confidence: 71%
“…16 Crown ethers have also been chosen for the pendant groups for polymer adsorbents for hazardous aqueous cations. 19 The adsorption capacity of Hg 2+ has been reported as 0.5-1.5 mmol g À1 , depending on the pH conditions. 19 These results suggest that a considerable number of ''sleeping'' sites are generally present during metal ion sorption by polymer materials.…”
Section: Hideaki Yoshitakementioning
confidence: 99%
See 1 more Smart Citation